A CRITICAL DISCOURSE ANALYSIS OF GENDER IDEOLOGY IN FEMININE, MASCULINE, AND UNISEX FASHION BRAND SLOGANS USING FAIRCLOUGH'S THREE-DIMENSIONAL MODEL - Rifki Juniar; Eka Fadilah (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2026)
. This study investigates gender ideology in feminine, masculine, and unisex fashion brand slogans using Norman Fairclough's Three-Dimensional Critical Discourse Analysis (CDA) model. It aims to identify the linguistic features used in the slogans, analyse students' interpretations of the slogans, and describe the gender ideologies the slogans reflect. Using a descriptive qualitative approach, the study analyses nine purposively selected fashion brand slogans representing feminine, masculine, and unisex branding, complemented by open-ended questionnaire data from twenty English Literature students at Universitas 17 Agustus 1945 Surabaya. The findings show that the slogans employ lexical choices, grammatical structures, metaphors, pronouns, evaluative adjectives, and gendered nouns to construct ideological meanings related to gender identity and consumer culture. Unisex slogans favour universal, inclusive expressions that promote equality and gender neutrality; feminine slogans foreground empowerment, inclusivity, and emotional authenticity; and masculine slogans construct masculinity through prestige, individuality, freedom, and sophistication. Students critically evaluated these representations of inclusivity and gender ideology, indicating that fashion brand slogans function as ideological discourse that reflects and reproduces broader social values regarding gender representation and consumer culture in contemporary society.